Level of anxiety among a sample of battered women in Gaza governorates - Elshafie, Alaa Maher (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to identify the level of anxiety and depression among a sample of battered women in the governorates of Gaza, and to uncover the relationship between anxiety and depression after the statistical analysis, The study used the descriptive method, and the study sample consisted of (130) battered women who are married and registered with the institutions and associations concerned with that category at the level of Gaza governorates. And to achieve the goals of the study, the researcher developed the anxiety scale and used the Depression Scale (Labik) (Al-Hussein, translation: Ahmed Abdel-Khalek, 2002). The results revealed that the level of anxiety among battered women in the governorates of Gaza was "average", and that the level of depression among them was high, and that the Pearson correlation between anxiety and depression was equal to (0.85), which is a direct correlation coefficient statistically significant at the level of (0.01), which means that whenever Increased anxiety increased depression. The researcher recommends the need to apply counseling programs to both husbands and wives in developing marital communication skills. Conducting training courses for those who are about to get married to learn how to manage marital life, and know the rights and duties.
Keywords: Anxiety; Depression; Abuse; Gaza